Bioactive food as dietary interventions for cardiovascular disease - Watson, Ronald R. (Ronald Ross); Preedy, Victor R. (Bioactive foods in chronic disease states., 2013)
One major example of the synergy of bioactive foods and extracts is their role as an antioxidant and the related remediation of cardiovascular disease. There is compelling evidence to suggest that oxidative stress is implicated in the physiology of several major cardiovascular diseases including heart failure and increased free radical formation and reduced antioxidant defences. Studies indicate bioactive foods reduce the incidence of these conditions, suggestive of a potential cardioprotective role of antioxidant nutrients. Bioactive Food as Dietary Interventions for Cardiovascular Disease investigates the role of foods, herbs and novel extracts in moderating the pathology leading to cardiovascular disease. It reviews existing literature, and presents new hypotheses and conclusions on the effects of different bioactive components of the diet. Addresses the most positive results from dietary interventions using bioactive foods to impact cardiovascular diseaseDocuments foods that can affect metabolic syndrome and other related conditions. Convenient, efficient and effective source that allows readers to identify potential uses of compounds - or indicate those compounds whose use may be of little or no health benefit. Associated information can be used to understand other diseases that share common etiological pathways.